(untitled) (Czech Journal of International Relations, 2024)
This special issue explores how popular culture shapes local, regional, national, and global perceptions of Ukraine amid the ongoing war with Russia. Integrating literatures on popular geopolitics, vernacular and aesthetic IR, and Ukraine studies, we delve into the complexities of the knowledge-making about Ukraine that takes place at the interstices of the everyday, the aesthetic, and the international. Given the mutually implicated relationship between popular culture and world politics, the popular representations of the Ukrainian subject both mirror and shape prevailing narratives, practices, identities, and power relations. But we also inquire into how popular culture serves as a space for political resistance and activism by those existing at the margins of world politics. By centering the Ukrainian perspective in all its multiplicity, the special issue helps to challenge the Western- and Russian-centric prism through which Ukraine has been approached in IR and related disciplines.